On Divisibility Property of Type 2 $(p,q)$-Analogue of $r$-Whitney Numbers of the Second Kind (European Journal of Pure and Applied Mathematics, 2023)
In this paper, the divisibility property of the type 2 $(p,q)$-analogue of the $r$-Whitney numbers of the second kind is established. More precisely, a congruence relation modulo $pq$ for this $(p,q)$-analogue is derived.
Keywords: Stirling numbers; Bell numbers; congruence relation; divisibility property; binomial transform; Hankel tranform; $r$-Whitney numbers; $r$-Dowling numbers